The Thermal Energy Storage Characteristics of Oleic Acid Modified ZnO‐Decorated Polymer Matrix‐Supported Composite Phase Change Materials: Synthesis and Characterization - Mehmet Selçuk MERT; Hatice Hande MERT (Macromolecular Materials and Engineering)
Abstract In this study, modified nano zinc oxide (ZnO)‐reinforced polymer‐supported novel thermally enhanced form‐stable composite phase change materials (PCMs) are presented, which are prepared via water in oil emulsion polymerization and following impregnation process steps. First, ZnO nanoparticles are modified with oleic acid (OA) to obtain lipophilic structures for emulsion stability, which are designed to take a role as a heat transfer activator. To ensure the shape stabilization of n‐hexadecane used as organic PCM, polymeric support materials are synthesized in the presence of modified ZnO nanoparticles (ZnO@OA). The polymeric frameworks exhibit open porous morphology, and the thermal stability of the support matrix improves with the addition of ZnO nanofiller. In the second step, composite PCMs are prepared by incorporation of n‐hexadecane with the solvent‐assisted vacuum impregnation method into polymer composites. The 1.0% ZnO@OA incorporated composite PCM has the highest incorporation ratio and exhibits a thermal storage capability (η) of 100%. According to the T‐history and thermal conductivity tests, it is observed that the heat conduction rate is enhanced with the addition of ZnO@OA nanofiller. The conclusion is that the obtained ZnO@OA integrated composite PCMs have a remarkable potential for latent heat storage applications requiring low temperature in the range of 5–25 °C.